IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING BASED ON MULTIPLE INTELLIGENCES (Case Study at Al-Azhar 45 Islamic Elementary School Palembang) - Fadhillah, Siti; Karolina, Asri; Tri Samiha, Yulia; Masuwd, Mowafg (Jurnal Asy-Syukriyyah, 2025)
This study examines the implementation of Islamic Religious Education learning based on Multiple Intelligences, focusing on linguistic and musical intelligences at Al-Azhar 45 Islamic Elementary School Palembang. Howard Gardner's theory of Multiple Intelligences offers a revolutionary perspective by recognizing that each individual possesses a unique combination of various types of intelligence. This qualitative research, employing a case study approach. Data were analyzed using Miles and Huberman's interactive model, incorporating triangulation techniques to ensure validity. The findings reveal that the implementation of learning begins with an observation of Multiple Intelligences to identify students' dominant intelligence profiles, followed by designing adaptive teaching modules. Development of linguistic intelligence is facilitated through reading, writing, storytelling, group discussions, and religious language games, while musical intelligence is developed through Islamic songs, melodic verse recitations, and the use of traditional instruments. Authentic assessment encompasses cognitive, affective, and psychomotor domains without employing ranking systems. The results indicate significant impacts on students' social attitudes, including seven noble character indicators: honesty, discipline, responsibility, tolerance, cooperation, courtesy, and confidence. Students demonstrate increased empathy, collaboration skills, respect for others' opinions, and confidence in expressing their ideas. Multiple Intelligences-based learning creates holistic, meaningful, and enjoyable learning experiences, enabling deep internalization of Islamic values that manifest in sustainable behavioral changes in students’ daily lives.